Calculation of Lighting Capacity on The Pinisi Tourist Ship Using the Zonal Cavity Method - Suardi, Suardi; Setiawan, Wira; Alamsyah, Alamsyah; Wulandari, Amalia Ika; Pawara, Muhammad Uswah; Raditya, Muhammad Yogi; Rifai, Muhammad (JMES The International Journal of Mechanical Engineering and Sciences, 2024)
Pinisi tourist ship is one of the tourist ship designs made to increase the interest of tourists to come to Taka Bonerate National Park. This tourist destination presents excellent maritime beauty, especially its coral reefs. Just like ships in general, pinisi also requires a supply of electricity, especially for use in lighting on board. This research aims to analyze the need for lighting power on board, by carrying out the concept of a tourist ship, the lighting system is also made like in a hotel with the aim of pampering tourists. In planning, the lighting system is made into two conditions, namely conditions during sleep and normal conditions. The type of lamp used is an LED lamp which is proven to be better than other types of lamps. The method used is the zonal cavity method or usually called the lumen method. The advantage of this method is that the power of the lights used in the room will be just right according to the needs of the room, neither more nor less, so it won't interfere with your eyesight because the lights don't feel dim or too bright. The results obtained were the following values for each Junction Lighting (JL), bottom deck (JL1) obtained a value of 0.419 kW, main deck (JL2) obtained a value of 1.058 kW, upper deck (JL3) obtained a value of 0.893 kW. The calculation value for the Junction Emergency (JE) was also obtained at 0.506 kW.